2021
DOI: 10.3390/genes12050766
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Snoring on Telomere Shortening in Adolescents with Atopic Diseases

Abstract: Atopic diseases can impose a significant burden on children and adolescents. Telomere length is a cellular marker of aging reflecting the impact of cumulative stress exposure on individual health. Since elevated oxidative stress and inflammation burden induced by chronic atopy and snoring may impact telomere length, this study aimed to investigate whether snoring would moderate the relationship between atopic diseases and telomere length in early adolescence. We surveyed 354 adolescents and their parents. Pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, a recent study has introduced compelling evidence about shorter telomere lengths (TLs) among patients with AR. TLs as biomarkers of aging are prompted shorten-ing by raised inflammation [47]. As a DNA repair protein, the ERCC1 may have influenced TLs wane procedure, such as sheltering them from homologous recombination [48], mediating a suppressive role in TLs maintenance by controlling the critical factor, TRF2 [49].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has introduced compelling evidence about shorter telomere lengths (TLs) among patients with AR. TLs as biomarkers of aging are prompted shorten-ing by raised inflammation [47]. As a DNA repair protein, the ERCC1 may have influenced TLs wane procedure, such as sheltering them from homologous recombination [48], mediating a suppressive role in TLs maintenance by controlling the critical factor, TRF2 [49].…”
Section: Discussionmentioning
confidence: 99%
“…Piñeiro-Hermida et al [ 101 ] found that mice with increased TS rates due to genetic deficiencies ( G3 Tert −/− mice) or induced by 6-thio-2′-deoxyguanosine administration exhibited eosinophilia and low circulating IgE levels and that TS affects the differentiation of club cells, which are essential for eliminating harmful substances inhaled into the lungs. Tung et al [ 102 ] proposed that snoring accelerates TS in atopic patients, primarily in those with asthma and allergic rhinitis; however, a limitation of this study was that it did not identify which immune cell population is more sensitive to increased TS. Moreover, an association has been found between the single nucleotide polymorphism MUC5B rs35705950 related to IPF predisposition and telomere shortening in leukocytes from two different cohorts.…”
Section: Influence Of Immune Cells With Shorter Telomeres On Development Of Lung Diseasesmentioning
confidence: 91%
“…Thus, the telomere has been referred to as a "mitotic clock" [12] and telomere length has been construed as a measure of "biological age" [13]. Consistent with these considerations, peripherally measured TL has been shown to be associated with a wide range of disease and health morbidities in adults [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and children [29][30][31][32][33][34][35][36][37][38] and has become a popular biomarker for stress and accelerated biological aging [10,35,[39][40][41][42][43][44][45]. Thus, TL at birth and the course of TL shortening in blood or saliva may provide insight into associated between premature birth and future health trajectory.…”
Section: Introductionmentioning
confidence: 99%